POTENSI LIMBAH SISIK IKAN LAUT SEBAGAI BAHAN KITOSAN DALAM PEMBUATAN BIOPLASTIK - Wica Elvina; Risnita Tri Utami; Dedi Pardiansyah; Yulfiperius Yulfiperius (University of Prof. Dr. Hazairin, SH, 2022)
State the objective is specific and clearly, as to what is to be obtained. Give a brief account of the methods. Identity scientific names of plants, another organism, and chemicals. State results succinctly. State conclusions or recommendations and link this to the significance of the work. The abstract must be integrated and independent which is consist of introduction and purpose, methods, results, conclusion, and suggestion. The abstract must be written using 150 until 200 characters which have no reference and accompanied keywords. It should be written using TIME NEW ROMAN 12 with line numbering.